2013
DOI: 10.2478/hepo-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Novel method of detection of phenylpropanoids of Rhodiola roots species

Abstract: S u m m a r yThe aim of the study was the identification and quantitative analysis of phenylpropanoid compounds in the roots of Rhodiola species. Rosavin, rosarin and rosin were determined in the roots of R. kirilowii and R. rosea from the field cultivation, Institute of Natural Fibres and Medicinal Plants. For the quantitative analysis, the ultra performance liquid chromatography -tandem mass spectrometry (UPLC-ESI MS/MS, Waters) was used. The results showed differences in the quantitative and qualitative ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…According to Olennikov et al [54], the main class of phenolic compounds in the underground organs of R. rosea is catechins: their concentrations are 10.84 and 61.30 mg/g in the roots and rhizome, respectively. Other investigators have shown that the level of catechins in the root can vary from 4.6 mg/g (in specimens from Poland [55]) to 20 mg/g (in specimens of Indian origin [56]). Judging by our data, the total concentration of catechins is on average 1.61 times higher in the root of R. rosea than in the rhizome (mainly because of compound No.…”
Section: Concentrations Of Hydroxybenzoic Acids and Catechinsmentioning
confidence: 99%
“…According to Olennikov et al [54], the main class of phenolic compounds in the underground organs of R. rosea is catechins: their concentrations are 10.84 and 61.30 mg/g in the roots and rhizome, respectively. Other investigators have shown that the level of catechins in the root can vary from 4.6 mg/g (in specimens from Poland [55]) to 20 mg/g (in specimens of Indian origin [56]). Judging by our data, the total concentration of catechins is on average 1.61 times higher in the root of R. rosea than in the rhizome (mainly because of compound No.…”
Section: Concentrations Of Hydroxybenzoic Acids and Catechinsmentioning
confidence: 99%